From E-Recruitment to Immersive Engagement: AI Models for Social and Human - ELMENZHI , Zenab; EL FASSI , Samia; KOBI , Hajar (Revue Internationale des Sciences de Gestion, 2026)
The convergence of artificial intelligence (AI), immersive technologies, and human-centered design is reshaping contemporary modes of interaction, learning, and organizational governance. Moving beyond traditional e-recruitment models, this paper offers a conceptual examination of how AI-driven immersive environments can foster more inclusive, ethical, and participatory forms of engagement within digital societies. Building on earlier frameworks such as Recruitment 4.0 and Smart Cities, Smart Talents, the study introduces the Immersive Engagement 5.0 model. This framework conceptualizes AI not merely as a technical or analytical tool, but as a socio-cognitive mediator shaping cognitive, emotional, and ethical dimensions of human–machine interaction. The model is structured around three interdependent pillars: Intelligent Mediation, Immersive Co-presence, and Ethical Orchestration, which together articulate a shift from functional interaction toward immersive and value-oriented digital experiences. Methodologically, the paper adopts a conceptual research design grounded in an interdisciplinary synthesis of literature from artificial intelligence, management studies, communication theory, and digital ethics. Institutional and organizational cases are mobilized illustratively to support theory-building rather than empirical generalization. The study contributes to ongoing debates on responsible AI and digital humanism by proposing a structured theoretical framework that informs the design of immersive, human-centric digital ecosystems and opens avenues for future empirical research.